漂移食用油油罐群的修复Resetting of drifiting edible oil tanks group - 左青1，李涵2，左晖3，付学华4 ZUO Qing1, LI Han2, ZUO Hui3, FU Xuehua4 (Zhongguo youzhi, 2023)
油罐区不同规格（30、50、100、500、2 000 t)的油罐在洪水冲击下罐体漂移到承台上面，油罐承台内沥青砂层出现空穴，罐顶连接栈桥撕裂变形，罐体连接管道变形和破裂，管线错位。结合施工实际，介绍了2 000 t油罐、500 t及以下油罐的修复工艺，并对重点工序（油罐基础垫层制作，油罐底板制作、铺设，油罐复位及锚定，油罐气密性及稳定性试验）进行了阐述。经过修复，油罐满足设计要求，可重新投入使用。 Oil tanks of different sizes (30, 50, 100, 500, 2 000 t) in the bulking area drifted above the bearing platform under flood impact, cavities appeared in the asphalt sand layer in the tank bearing platform, the tank top connecting trestle was torn and deformed,the tank coupling pipeline was deformed and ruptured, and the pipeline was misaligned. In conjunction with the actual construction, the resetting processes for 2 000 t tank, 500 t tank and below were introduced, and the key processes (construction of foundation cushion, bottom plates fabrication and laying, resetting and anchoring, gas tightness and stability test of oil tanks) were described. After the resetting, the oil tanks meet the design requirements and can be put back into service.